Molecular biology of ryanodine receptors: an overview - George, Christopher; Lai, F. Anthony (Henry Stewart Talks, 2007)
Molecular cloning of RyR, The identification of functional domains, RyR channel structure, Channel regulation by: a) inter-RyR interaction, b) divalent cations and c) protein:protein interactions, The role of leucine zippers in assembling the 'macromolecular complex', Defective protein:protein interactions in cardiac disease, Genetic basis of RyR dysfunction, Identification of mutations in cardiac RyR, Functional characterization of RyR mutations, Investigating interdomain interactions using state-of-the-art imaging tools, Pathological defects in channel stability
Reviewed at 2022/05/09